Ophthalmic grading of facial paralysis: need for a closer look. Issue 9 (6th January 2015) - Ziahosseini, Kimia; Nduka, Charles; Malhotra, Raman
Abstract : Very many variations of facial grading systems have been developed, but none address the ophthalmic complications of facial nerve weakness adequately. The important priorities for ophthalmic surgeon are protecting the ocular surface, maintaining sight and peripheral vision, as well as improving the cosmesis of periocular area. The absence of a universally agreed grading system on the ophthalmic plastic complications of facial nerve paralysis is an obstacle to standardised treatment. It is time for clinicians to recognise this need.